2022
DOI: 10.1155/2022/1088393
|View full text |Cite|
|
Sign up to set email alerts
|

Design of Intelligent Nursing Decision Support System Based on Multiattribute Decision Model

Abstract: Nursing medical histories are copied randomly, leading to the occurrence of incorrectly altered histories, and medical errors are on the rise year by year. Moreover, erroneous falsification of nursing medical history is a challenging issue that needs to be urgently addressed in domestic nursing medical history. In this manuscript, a caregiver association method, which is based on a multiattribute decision model, is proposed which is specifically designed for the caregiver association selection problem in intel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…In [24], they developed an edge computing-based DSS for basketball movement recognition. The system utilized an RNN to analyze player movements and classify them into actions such as dribbling, passing, and shooting.…”
Section: Related Workmentioning
confidence: 99%
“…In [24], they developed an edge computing-based DSS for basketball movement recognition. The system utilized an RNN to analyze player movements and classify them into actions such as dribbling, passing, and shooting.…”
Section: Related Workmentioning
confidence: 99%
“…Spreckelsen et al [1] described a CDSS implemented in PDAs as a system in which a knowledge base is embedded to deliver the required knowledge and monitor given therapy plans for physicians at the point of care. Recent work on mobile clinical support systems addresses different decision support such as knowledge delivery on demand, medication consultant, therapy reminder [1][2], preliminary clinical assessment for classifying treatment categories [2][3], and providing alerts of potential drugs interactions and active linking to relevant medical conditions [4]. Studies have demonstrated that CDSS can be an efficient means for decreasing errors or omissions and improving adherence to practice guidelines.…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi, as publisher, following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of systematic manipulation of the publication and peer-review process.…”
mentioning
confidence: 99%